Multilingualism as a Principle of the EU Court of Justice - K. Kh. Rekosh (Vestnik MGIMO-Universiteta, 2014)
Since the jurisprudence reflects relations between the institutions, bodies and organizations of the EU and native speakers, the EU Court of Justice plays a huge role in shaping the legal discourse. Relations between the EU and citizens show the effectiveness of the principle of multilingualism, that is apparent before the Court. The enlargement of the Union to 28 member States and, accordingly, the increase of the number of official languages to 24 complicate the implementation of the principle of multilingualism and create many problems for the EU Court of Justice: legal, linguistic, budget, translation. All documents of the Court are not translated into 24 EU official languages completely and often limited to summaries. All documents are translated only into French and proceeding languages, for the scale of the translation work have a direct impact on the timing of legal proceedings. To provide help in written translations, much work is carried out in the Court on drawing up dictionaries, thesauri, where multilingualism is fully manifested. On the use of languages and language regime, There is an extensive legal practice, however, the term «multilingualism» is not used by the Court, despite the recognition of the principle of equality of all official languages, perhaps, due to the fact that the Court itself not always follows it. The article shows that multilingualism as a legal concept and principle opens up, sometimes adjacent to the already distinguished objects of regulation, new areas of legal research. Comparison of legal solutions to the problems of multilingualism in different states with a variety of languages, law and order, or in international organizations, lays basis of "comparative linguistic law" Now in the doctrine of law of the European Union neither the linguistic law, nor the comparative linguistic law do not exist, but to provide cooperation in the field of justice and mutual recognition of judicial decisions on the basis of the principle of multilingualism, the EU has adopted the Directive on the right to interpretation and translation in the framework of criminal proceedings.